Indonesian online media’s construction of "maritime" : a critical discourse analysis - Saddhono, Kundharu (Array, 2020)
The concept of maritime (maritime) is frequently discussed among the Indonesian people, a fact that may be attributed to the emphasis that has been given to maritime issues by President Joko Widodo since his candidacy. This article applies Faircloughian approach to critical discourse analysis (CDA) to understand the coverage of ‘maritime’ in Indonesian online media. This paradigm has been selected because the media does not simply act as a neutral medium through its publication and coverage; rather, media have specific ideologies, which can be described and analyzed through critical discourse analysis. This approach focuses on three aspects when analyzing written discourses: representations, relations, and identities. Representation refers to specific words and grammatical structures to construct reality; relations refer to the connections between the subjects as depicted in the discourse; and identity refers to reporters’ positions in their coverage of online media, including their biases. In general, relations and identities in Indonesian online media coverage have been oriented towards the government and society. The government has been constructed ambiguously by online media, but depictions of government have tended to be positive, with a focus on the success of its maritime programs.